Effect of Different Quick-freezing Temperatures on Quality Characteristics and Microstructure of Zigui Navel Orange Fruit Tissue - Liuyan WANG; Jingnan REN; Yuqing QIN; Gang FAN; Siyi PAN; Zhenglun LI; Zhaoxing HU; Xiang HE (Shipin gongye ke-ji)
In this study, in order to improve the quality of quick-frozen Zigui navel oranges, they were processed at varying quick-freezing temperatures (−20, −30, −40, −50, −60, −70 and −80 ℃). On the flesh and peel of Zigui navel orange to assess the influence on edible quality, vitamin C, bioactive compounds, antioxidant properties, water status and distribution, and microstructure. The results indicated that flesh frozen quickly between −60 ℃ and −80 ℃ exhibited enhanced texture, bioactivity, and antioxidant activity. Additionally, flesh frozen at −80 ℃ experienced the shortest phase transition period and maintained a moisture state and distribution most similar to fresh flesh. Quick freezing at −40 ℃ and −50 ℃ could well preserve the flesh's vitamin C content, color, and flavor. The peel with quick freezing at −70 ℃ and −80 ℃ had higher vitamin C content, color, texture, antioxidant activity and bioactive compounds. Furthermore, the peel that was quickly frozen at −80 ℃ showed the shortest freezing time and the closest microstructure to the control group. In summary, the optimal quick-freezing temperature range for Zigui navel orange flesh is from −40 ℃ to −80 ℃, and for the peel, it is from −70 ℃ to −80 ℃. These findings are crucial for the comprehensive assessment, further investigation, and advancement of quick-frozen navel orange fruit products.